2022
DOI: 10.2147/idr.s346494
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Carbapenem-Resistant Organism Bacilli from Liver Transplantation Donors – Single Center Experience

Abstract: To evaluate and explore the effectiveness of the new prevention and control measures for the donor-derived infection (DDI) associated with CRO after liver transplantation. Methods: The data of 120 organ donors and recipients from January 2018 to May 2020 were retrospectively analyzed at The Liver Transplantation Center of Beijing Youan Hospital, Capital Medical University, to investigate the epidemiological status of CRO in donors. The cases were divided into two groups. The implemented group was treated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…Notably, incidence of DDI due to CRE is high in China, one study focused on KT patients reported that possible DDI increased the risk of CRE infection by more than six times [75]. Authors reported varying prevalence rates of CRE among donor or preservation fluid cultures, ranging from 1.6% to 19.2% [93][94][95].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
“…Notably, incidence of DDI due to CRE is high in China, one study focused on KT patients reported that possible DDI increased the risk of CRE infection by more than six times [75]. Authors reported varying prevalence rates of CRE among donor or preservation fluid cultures, ranging from 1.6% to 19.2% [93][94][95].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%